2018
DOI: 10.3390/met8060387
|View full text |Cite
|
Sign up to set email alerts
|

Liquation Cracking in the Heat-Affected Zone of IN738 Superalloy Weld

Abstract: Abstract:The main scope of this study investigated the occurrence of liquation cracking in the heat-affected zone (HAZ) of IN738 superalloy weld, IN738 is widely used in gas turbine blades in land-based power plants. Microstructural examinations showed considerable amounts of γ' uniformly precipitated in the γ matrix. Electron probe microanalysis (EPMA) maps showed the γ-γ' colonies were rich in Al and Ti, but lean in other alloy elements. Moreover, the metal carbides (MC), fine borides (M 3 B 2 and M 5 B 3 ),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 44 publications
(71 reference statements)
1
12
0
Order By: Relevance
“…Previous research works have thoroughly investigated the influence of chemical composition and microstructure resulting from different thermal treatments on the hot cracking susceptibility of alloy 718 [9,[14][15][16][17][18] and alloy 738 [19]. This has led to contradictory conclusions about the influence of grain size on the hot cracking susceptibility of alloy 718 castings.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research works have thoroughly investigated the influence of chemical composition and microstructure resulting from different thermal treatments on the hot cracking susceptibility of alloy 718 [9,[14][15][16][17][18] and alloy 738 [19]. This has led to contradictory conclusions about the influence of grain size on the hot cracking susceptibility of alloy 718 castings.…”
Section: Introductionmentioning
confidence: 99%
“…Since these alloys are not optimized for additive manufacturing, processing is challenging. Specifically, the high amount of γ’ precipitates (up to 80 vol.%) and the strong tendency for segregation lead to a high susceptibility for cracks including solidification cracking [ 16 ], liquation cracking [ 17 ] or strain age cracking [ 18 , 19 ]. Recent studies have shown that apart from alloy modifications [ 20 , 21 , 22 ], either a high amount of high angle grain boundaries or no high angle grain boundaries at all (single crystalline, SX) are necessary to process these alloys without cracks [ 8 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Preheating is usually recommended by the welding community to limit thermal gradients (K/m) during cooling, thus improving the material's resistance to hot cracking. [12] Preheating temperature and time, i.e., the influence of short-term heat treatment cycles on nickel superalloy's microstructure changes, is a particularly important area in designing new technologies, as welding processes are widely used for regenerating foundry defects and repairing of serviced components. [13][14][15][16] Hot cracking, including liquation cracking in the heat-affected zone, is directly dependent on the c¢ behavior during heating and subsequent cooling.…”
Section: Introductionmentioning
confidence: 99%